Tumor microenvironment-responsive hyperbranched polymers for controlled drug delivery - Yuqiong Guo; Xinni He; Gareth R. Williams; Yue Zhou; Xinying Liao; Ziyi Xiao; Cuiyun Yu; Yang Liu (Journal of Pharmaceutical Analysis)
Hyperbranched polymers (HBPs) have drawn great interest in the biomedical field on account of their special morphology, low viscosity, self-regulation, and facile preparation methods. Moreover, their large intramolecular cavities, high biocompatibility, biodegradability, and targeting properties render them very suitable for anti-tumor drug delivery. Recently, exploiting the specific characteristics of the tumor microenvironment, a range of multifunctional HBPs responsive to the tumor microenvironment have emerged. By further introducing various types of drugs through physical embedding or chemical coupling, the resulting HBPs based delivery systems have played a crucial part in improving drug stability, increasing effective drug concentration, decreasing drug toxicity and side effects, and enhancing anti-tumor effect. Here, based on different types of tumor microenvironment stimulation signals such as pH, redox, temperature, etc., we systematically review the preparation and response mechanism of HBPs, summarize the latest advances in drug delivery applications, and analyze the challenges and future research directions for such nanomaterials in biomedical clinical applications.